Analisis Kualitas Pelayanan Rusunawa Flamboyan Cengkareng Terhadap Kepuasan Penghuni - Herawaty, Mety Titin; Zahra, Zahra (Universitas Medan Area, 2023)
This study analyzes the quality of service provided by Rusunawa Flamboyan. Answering residents’ complaints, conducting evaluations, and developing service quality standards are the problems discussed in this study. This research is quantitative and uses the Servqual method with 50 respondents and 50 questionnaires that have been subjected to validity, reliability, and hypothesis tests. In testing using the Servqual method on residents of Rusunawa Flamboyan Cengkareng, it was found that they had an average perception of 3.72 on the five dimensions of Servqual, while the expected value was 3.36. Thus, there is a difference of 0.36, which is positive, indicating that the services in the five Servqual dimensions have met the residents’ expectations. Furthermore, improvements to facility evaluation, identification of areas of improvement, and setting clear service quality standards are points that can continue to be encouraged.